Hubungan Agama dan Negara dalam Perspektif Dr. Yusuf Al-Qaradhawi - Baderan, Suprisno (Farabi, 2024)
This article examines the political thought of Yusuf Al-Qaradhawi, including the relationship between religion and the state in the context of Muslim society. Al-Qaradhawi is an Islamic scholar who has influenced considerable contributions in contemporary Islamic thought, particularly in issues related to politics and Islamic law. This article presents Al-Qaradhawi's understanding of key concepts such as sharia, democracy, human rights, and the role of religion in the political order. In addition, it examines Al-Qaradhawi's views on how religion and the state can interact in a pluralistic and modern society. This research outlines the impact of Al-Qaradhawi's thought in the context of political development in the Islamic world and its relevance in facing current social and political challenges.